1992
DOI: 10.1002/hc.520030422
|View full text |Cite
|
Sign up to set email alerts
|

Dialkyltin derivatives of dicarboxylic acids: Synthesis, characterization and in vitro antitumor properties

Abstract: Diorganotin deriuatiws of dicarboxylic acids, including diethyltin propene-l,3-dicarboxylate, diethyltin homophthalate, and di-n-butyltin tetrafluorophthalate, were tested in uitro against two human tumor cell lines, MCF-7, a mammary tumor, and WiDr, a colon carcinoma. Most of these display lower inhibition doses ID,, than cis-platin. The synthesis and characterization of the last three compounds by Mossbauer spectroscopy, 'H, I3C andlor Il9Sn NMR and mass spectrometry, are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…In an encouraging number of instances, the results show the organotins to be more effective than cis-platin or carboplatin (3). Studies of structureactivity relationships have shown that the factors influencing activity may be very subtle differences in bond lengths or bond angles, reinforcing the value of structural investigations in this field (10)(11)(12)(13). Recent reports of the activity of certain diorganotin derivatives of pyridine 2,6-dicarboxylic acid and some related compounds (14,15) against the P388 lymphocytic leukemia tumour, both in vitro and in vivo, led us to report the synthesis and characterization of a series of diorganotin iminodiacetates (16) and diorganotin(1V)-N-arylidene-a-amino acid complexes (17).…”
Section: Introductionmentioning
confidence: 91%
“…In an encouraging number of instances, the results show the organotins to be more effective than cis-platin or carboplatin (3). Studies of structureactivity relationships have shown that the factors influencing activity may be very subtle differences in bond lengths or bond angles, reinforcing the value of structural investigations in this field (10)(11)(12)(13). Recent reports of the activity of certain diorganotin derivatives of pyridine 2,6-dicarboxylic acid and some related compounds (14,15) against the P388 lymphocytic leukemia tumour, both in vitro and in vivo, led us to report the synthesis and characterization of a series of diorganotin iminodiacetates (16) and diorganotin(1V)-N-arylidene-a-amino acid complexes (17).…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10] Several papers deal with complexes of various metals containing the carboxylates of iminodiacetic acid, N-methyliminodiacetic acid and some other N-substituted iminodiacetic acids as main ligands. 7,[11][12][13][14][15][16][17][18][19] Among the compounds of Scheme 1, 6,7,19 Ia and Ib did not exhibit any activity in vivo against P388 leukaemia. 6 Compounds Ia, If, Ih, Ii and Ij have been tested in vitro against two human cell lines, MCF-7, a mammary tumour, and WiDr, a colon carcinoma.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5] However, diorganotin(IV) derivatives of bis(carboxymethyl)amines and some N-substituted analogues have been investigated only to a limited extent. 6,7 This is probably due to the fact that only some ligands are commercially available and methods for their preparation are not numerous. [8][9][10] Several papers deal with complexes of various metals containing the carboxylates of iminodiacetic acid, N-methyliminodiacetic acid and some other N-substituted iminodiacetic acids as main ligands.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3][4][5] Di-n-butyltin perfluoroalkanecarboxylates also exhibit significant activities in vitro (H. Dalil, M. Biesemans, J. C. Martins, J.-M. Renon, B. Mahieu, D. de Vos, R. Willem and M. Gielen, unpublished results) When dicarboxylic acids react with a diorganotin oxide, they generally lead to a cyclic structure including one tin atom. 6,7 In this paper we investigate whether a rather rigid dicarboxylic acid can give rise upon condensation with di-n-butyltin oxide to a strained cyclic diorganotin dicarboxylate. Hexafluoro-2,2-bis(4-carboxyphenyl)propane 1 was found appropriate for this purpose.…”
Section: Introductionmentioning
confidence: 99%